The use of bacteriophage therapy for curing the Escherichia coli 0157 infection in mice - Metha Restu, Rio Rendy, Hera Nirwati, Susi Iravati, Mova Aria, Ida Ayu Putu (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Diarrhea is still a problem in public health, especially in developing country such as Indonesia. Escherichia coli 0157:H7 {Enterohemorrhagic Escherichia coli (EHEC)} is one of the important strains as the etiology of bloody diarrhea with sistemic complications such as hemolytic uremic syndrome and hemorrhagic colitis. The increase in the discovery of E. coli 0157:H7 resistance to antibiotic is a worldwide problem that must be solved. Bacteriophage application can be a promising alternative therapy. In addition, bacteriophage can also be used as diagnostic tool for bacterial identification and as biocontrol agent in bacterial water pollution.ObJective: The aim of this study was to isolate and identify a specific bacteriophage using a specific strain of E. coli 0157 and use this bacteriophage to cure the E. coli 0157 infection in mice.Methods: E. coli was isolated and identified from faecal samples of diarrheal patients from many Primary Health Centers in Yogyakarta, using McConkey Agar and biochemical media. E. coli 0157 was determined using sorbitol McConkey Agar and agglutination test. Toxins of these strains were detected using hemolysis assay method. Bacteriophage was isolated using one of E. coli 0157 strain (E. coli K-151) from river water of Kali Mambu. The therapeutic effect of this bacteriophage was studied using eighteen threemonth-old male mice of Swiss strain. They were classified randomly into three groups (6 groups). Mice in group A and B were infected with 0.5 ml of 108 CFU of E. coli suspension orally. Only mice in group A were treated with bacteriophage 1.10"pfu/mL, while those in group B were not treated, and group C was used as control.Results: Three strains of E. coli 0157 (K-151, K-840 and K-854) were isolated among 70 E. coli isolates. Bacteriophage K-151 was isolated from the river water. Average cure duration in the group who was given phage K-151 therapy was 34.17 hours, and average cure duration in the group that was not given phage K-151 therapy was 72.7 hours. The mortality rate of group A was 0%, while in group B was 17%. Conclusion: Bacteriophage is effective as alternative therapy against E. coli infection in mice.Keywords: E. coli 0157 - bacteriophage - hemolysis assay - diarrhea